Inhibition of nitric oxide synthase activity and chemokine (CXCL12) supplementation can improve hematopoietic reconstitution in mice lethally irradiated by 60Co gamma radiation - Daniel Perez Vieira; Andrés Jimenez Galisteo Jr.; Heitor Franco de Andrade Jr. (Brazilian Journal of Radiation Sciences)
Reduction of nitric oxide (NO) production is related to increased survival in some models of infection and ionizing radiation (IR) exposure. The work used lethally irradiated (60Co, 8Gy) C57Bl6j mice, treated or not with aminoguanidine (AG), an inhibitor of an isoform of nitric oxide synthase (iNOS). Also tested iNOS-/- knockout mice and a distinct group treated intraperitoneally with synthetic CXCL12, a homing chemokine related to hematopoietic reconstitution after IR exposures. Aminoguanidine treatment lead to an overshoot of proliferation of hematopoietic CD34+ cells in bone marrows (2nd day after IR) and spleens (2nd to 4th day after IR) of irradiated mice, showing a compensative response of these organs against deleterious effects of radiation. CXCL12 mRNA production was increased in spleens of AG-treated mice at 2nd day after IR, but not in other periods neither in bone marrows. CXCL12 administration did not alter CD34+ counts but seemed to keep circulating platelet counts in levels comparable to controls. Thus, CXCL12 and AG administration could help on bone marrow repopulation after critically exposed individuals.